GREEK AND ROMAN MYTHOLOGIES’ CHARACTERIZATIONS AS SIGN ASSOCIATED WITH ROWLING’S HARRY POTTER AND THE SORCERER’S STONE - Luthfia, Karina Hanum (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2014)
The objective of the study are to outline the characterization of Harry Potter and the Sorcerer’s Stone reflecting on Greek and Roman mythologies’ characterizations, to find out Greek and Roman mythologies’ characterizations associated with Harry Potter and the Sorcerer’s Stone, and to explain the author’s idea expressions in revealing the revival of Greek and Roman mythologies associated with the novel. The research methodology used the descriptive research. Descriptive research can be used to identify and classify the elements or characteristics of a subject. Quantitative technique are most used to collect, analyze, and summarize data. For instance: the analysis of symbolism. The results of the research are that Harry Potter and the Sorcerer’s Stone characterization was considered as the sign to the Greek and Roman mythologies’ characterizations, the characterization on Harry Potter and the Sorcerer’s Stone was associated with the characterization on Greek and Roman mythologies, and Rowling conveyed her ideas that were expressed in delivering the mythologies. The Rowling’s ideas expressed in the characterization naming, the characterization development on Greek and Roman mythologies, and in her personal life.